Digital Marketing: An Empirical Examination on Awareness and Perception onIntrusive Marketing Strategies - P.S, Buvaneswari; M.S, Swetha (International Journal of Engineering and Technology, 2018)
Technological, social & cultural changes have paved way for changes in marketing strategies adopted by the corporates for sustainability. The new technologies adopted by the companies have enabled intrusive form of marketingÂ allowing them to market their products without having the consent of the target group. With increase in number consumers using devices to buy product or service it is pertinent for the firms to forecast the trends and strategize their marketing plans which will increase the chances of success in future. This study will try to identify the level of awareness on the invasive strategies and how consumers react to such technologies and advertisements, through an empirical research.Â